2006
DOI: 10.1590/s1516-89132006000300011
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of Kalliapseudes schubartii in unvegetated soft bottoms of the estuarine region of the Lagoa dos Patos

Abstract: Studies were carried iut on seasonal mortality by taking samples of Kalliapseudes schubartii (Crustacea: Tanaidacea) for a year in the estuarine region of the Lagoa dos Patos (southern Brazil). Results demonstrated no significant difference in seasonal mortality rates, which suggest that populations of K. schubartii was heavily preyed on year round and that an assumption of a significantly higher mortality in summer/autumn than in spring/winter might not be held in unvegetated soft bottoms of the estuarine reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
3
0
2
Order By: Relevance
“…The author has associated the latter result with the hatching season of insect larvae that could act as predators of tanaids in summer months. Fonseca & D'Incao (2006) reported that the mortality rates of K. schubartii did not differ between sampled seasons at Patos Lagoon. However they agree that this tanaid species might be heavily preyed by juvenile fishes and decapods; and that the expected higher mortality in summer/spring might not apply to unvegetated soft bottom estuaries.…”
Section: Discussionmentioning
confidence: 97%
“…The author has associated the latter result with the hatching season of insect larvae that could act as predators of tanaids in summer months. Fonseca & D'Incao (2006) reported that the mortality rates of K. schubartii did not differ between sampled seasons at Patos Lagoon. However they agree that this tanaid species might be heavily preyed by juvenile fishes and decapods; and that the expected higher mortality in summer/spring might not apply to unvegetated soft bottom estuaries.…”
Section: Discussionmentioning
confidence: 97%
“…The first highest point was used to estimate each regression line. Capture curves were estimated for each sex and region separately and compared by covariance analysis (ANCOVA) (Fonseca & D’Incao, 2006; Keunecke et al, 2007). Also, Z was defined as the sum of the fishing mortality coefficient (F) caused by fishing operations, and the natural mortality coefficient (M) that includes predation, competition, disease, and adverse environmental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…There are 39 species in the primarily circumtropical family Kalliapseudidae [ 7 ], which was inferred to be monophyletic on the basis of three molecular loci [ 8 ]. Members of this family, in addition to being deposit feeding as other tanaidaceans, are thought to be filter feeders based on the rows of long plumose setae on their chelipeds [ 9 , 10 ]. F. P. P. Leite and P. E. P. Leite [ 11 ] provided evidence that Kalliapseudes gianucai , described by Bacescu [ 12 ] and known only from the type locality in the state of Rio Grande do Sul, Brazil, represents a dimorphic male stage and is thus a synonym of M. schubarti .…”
Section: Introductionmentioning
confidence: 99%